2021
DOI: 10.1111/are.15479
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel catalase gene and its response to low temperature stress in noble scallop Chlamys nobilis with different total carotenoids content

Abstract: Huge temperature fluctuation has great deleterious effects on marine invertebrates (Hennig & Andreatta, 1998). Under extreme conditions, DNA, lipids and proteins would be damaged by excessive reactive oxygen species (ROS) (Evans & Halliwell, 1999). To maintain the redox balance, marine invertebrates have evolved a very complex antioxidant system to eliminate ROS, which includes many antioxidants enzymes and non-enzymatic antioxidants, for example catalase (CAT), superoxide dismutase (SOD) and carotenoids (Abele Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In the present study, induced CAT activity and higher Hdh-CAT mRNA expression levels were observed in response to thermal stress. Similar findings have been previously reported for CAT in scallop [4], ark shell [21], Mediterranean mussel [60], and Pacific oyster [61]. The present study also found elevated ROS levels in thermal-stressed abalone, consistent with previous findings of American oyster [31].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, induced CAT activity and higher Hdh-CAT mRNA expression levels were observed in response to thermal stress. Similar findings have been previously reported for CAT in scallop [4], ark shell [21], Mediterranean mussel [60], and Pacific oyster [61]. The present study also found elevated ROS levels in thermal-stressed abalone, consistent with previous findings of American oyster [31].…”
Section: Discussionsupporting
confidence: 93%
“…Present findings suggest that Hdh-CAT might play a role in the antioxidant defensive mechanism against ROS generation induced by H 2 O 2 . Another antioxidant, SOD, has been previously recommended as an antioxidant defender against H 2 O 2 -induced damage in Pacific abalone [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations